Kontrol Diri pada Mantan Pecandu Narkoba: Sebuah Studi Fenomenologi - Thalib, Tarmizi; Koanda, Naftalen; Lestari, Ermitha; Yumna, Andi S.; Muhajrah, Muhajrah; Abdurrachman, Nur A. K. (Lembaga Pengembangan Kinerja Dosen, 2024)
Cessation of drug use and recovery from drug addiction is a complicated process and takes a long time, so it is not uncommon for a former drug addict to experience a relapse. This research aims to describe the description and aspects of self-control in former drug addicts as part of the recovery process. The research method used in this research is qualitative with a phenomenological approach. The subject is a male (26 years old) former addict who did not attend formal rehabilitation. Data was obtained by observation and interviews. Based on the results of the research analysis, it was found that the subjects behavioral control, cognitive control and decesional control so as not to use drugs again. The subject also received external encouragement from family and people around him.